Orator Apostolicus as theoretician of war and peace : A hitherto unknown manuscript treatise de bello et pace by Iohannes Staphileus (1472–1528) - Novaković, Darko (2012)
Ivan Štafilić (Stafilić; Ioannes Staphileus /Staphylaeus/ : Traù 1472 – Rome 1528), Professor of Canon Law at La Sapienza in Rome, Auditor Sacrae Rotae and the Bishop of Sebenico from 1512 until his death, was a diplomat of the Holy See who served during the pontificate of four different Popes, namely Julius II, Leo X, Adrian VI and Clement VII. In addition to his printed works: Excidii urbis Romae sub annum Christi MDXXVII caussa. Oratio ad Rotae auditores habita (s. l. et a.; Strasburg, 1528?); Tractatus de gratiis expectativis (posthumously, Venice 1540; Paris, 1547; Paris, 1557; Lyon 1573 etc.), various manuals, dating already from the 16th century to present time (Gessner, Simmler, Possevino, Ljubić etc.), also mention his lost work De bello et pace dedicated to the Croato-Hungarian King Ladislaus II. Codex preserved in the library of the Toledo Cathedral (Archivo y Biblioteca Capitulares ms. 41,3) which I have been able to consult in the microfilm format confirms the existence of this tractate by Štafilić. However, it is not dedicated to Ladislaus II but to his brother, the King of Poland and the Grand Duke of Lithuania, Sigismund I. As papal envoy Štafilić attended the wedding of Sigismund I to Barbara Zápolya in 1512 and made a speech on this occasion. Štafilić presented his discourse under five separate and short headings: 1.When in the distant past did the first wars start? Were they subject to any laws? What were their outcomes? How many types of war can be defined? (fols. 7–39) 2. Which are just causes for opening of, or responding to the hostilities? Under which circumstances can the war be deemed just? (fols. 39–67) 3. Who is entitled to declare war? Who can freely take part and fight without committing a sin? (fols. 67–76) 4. Who is entitled to material spoils of war? Are those who obtained such spoils free to retain them with clear conscience? (fols. 76–103) 5. Can the warring parties be forced to cease the conflict and conclude peace? In such an event, who is the suitable or sufficiently eminent mediating authority? (fols. 103–127) In addition to the theoretical dimension of this tract and the sources referred to by the learned doctor utriusque iuris the attention should be given to anti-Ottoman digressions which show Štafilić’s understanding of then current political and military situation of the Western Christendom. Furthermore, his awareness of his own roots is also remarkable and evidenced not only in the name attribute at the start of the discourse (Ioannes Staphileus Dalmata but also in the laudatory invocation at its end (Laus Deo et Beatae Virgini ac Divo Hieronymo conterraneo nostro. Amen).